Experimental Study on Springback Properties of 6061 Aluminum in V-Bending - Ahmed Ozan Örnekci; Seçil Ekşi (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Sheet metal bending is one of the most commonly applied methods among sheet metal forming operations. In this study, the springback behavior of aluminum alloys of different thicknesses was examined by performing v-bending processes at different die angles and widths. The experiments were carried out on 1 and 1.5 mm thick plates at die angles of 140°, 150° and 160° and three different die widths: 10 mm, 16 mm and 20 mm. In this experimental study, it was observed that springback decreased as the die width increased. As the die angle increased, springback values also increased. It has been observed that sheet thickness has little effect on springback. As the sheet thickness increased, the amount of springback decreased. The lowest springback value of 0.1° was obtained in the 1.5 mm thick specimen with a die width of 10 mm and a die angle of 140°. The highest spring-go value of -2.7° was obtained in the 1 mm thick specimen with a die width of 20 mm and a die angle of 140°. As a result of the variance (ANOVA) analysis, it was seen that the die width had a more significant effect (78.42%) on springback than the die angle. The effect of die angle on springback is 10.73%. As a result of the experiments and statistical analysis, it was seen that the parameter that most affects springback is die width.